(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
Neogloboquadrina acostaensis, typical Tortonian taxon, was found in Upper Serravallian sediments in a core collected in the southern offshore of Sicily. Whether the FAD of this taxon is to be considered older is here questioned.